Approach for Designing Human-Centered and Energy Saving Lighting Luminaires - Jwo-Huei Jou; Zhe-Kai He; Deepak Kumar Dubey; Yi-Fang Tsai; Snehasis Sahoo; Yu-Ting Su; Chun-Hua Wu (Photonics, 2022)
Electric light has been widely adopted in numerous applications, including signage, display, and illumination. Enhancing its efficiency and quality has been the focal point until now. Long exposure to intensive blue-light-enriched white light is, however, likely to cause health concerns, such as retina damage and melatonin suppression. A good light should hence be redefined as, at least, human-friendly, besides energy-saving and high-quality. Here, we demonstrate a novel design approach toward a good light based on the state-of-the-art solid-state lighting technologies. Taking the typical phosphor converted white-light-emitting diode (LED) for lighting, for example, a 2000 K orange-white emission with a black-body-radiation chromaticity can be 5 times safer than the 5000 K pure-white counterpart from a retina-protection perspective and 3.9 times safer from an MLT-secretion perspective. Further tuning its chromaticity from black-body-radiation- to sunlight-style, the 2000 K LED can be made 303% safer in terms of maximum retina permissible exposure limit or 100% better in terms of melatonin suppression sensitivity. Moreover, its corresponding efficacy limit can be increased from 270 to 285 lm/W, while keeping light quality constant at 91, in terms of natural light spectrum resemblance index. The same approach can be extended to organic LED as well as the design of a good light for display, wherein pure-white emission with a color temperature around 6000 K is suggested to replace the bluish-white backlight to safeguard human health.